2007
DOI: 10.1007/s11664-007-0170-0
|View full text |Cite
|
Sign up to set email alerts
|

Improved Schottky Contacts on n-Type 4H-SiC Using ZrB2 Deposited at High Temperatures

Abstract: We report on improved electrical properties and thermal stability of ZrB 2 Schottky contacts deposited on n-type 4H-SiC at temperatures between 20°C and 800°C. The Schottky barrier heights (SBHs) determined by current-voltage measurements increased with deposition temperature, from 0.87 eV for contacts deposited at 20°C to 1.07 eV for those deposited at 600°C. The Rutherford backscattering spectroscopy (RBS) spectra of these contacts revealed a decrease in oxygen peak with an increase in the deposition tempera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 39 publications
2
12
0
Order By: Relevance
“…The O level dependence on deposition temperature can be explained by the known physical fact that desorption of O, or rather OH, from surfaces is favored by higher temperatures. This is in agreement with Oder et al [27] who reported that the O concentration in ZrB2 films decreased when the deposition temperature was increased from 20 °C to 600 °C.…”
Section: Chemical Bonding Structure and Elemental Compositionsupporting
confidence: 93%
See 1 more Smart Citation
“…The O level dependence on deposition temperature can be explained by the known physical fact that desorption of O, or rather OH, from surfaces is favored by higher temperatures. This is in agreement with Oder et al [27] who reported that the O concentration in ZrB2 films decreased when the deposition temperature was increased from 20 °C to 600 °C.…”
Section: Chemical Bonding Structure and Elemental Compositionsupporting
confidence: 93%
“…Oder et al [27] suggest that the O originates from oxides on the substrate surface and that the reason for the decreased O content in films deposited at higher temperature is that the O at the film surface is removed by the formation of B2O3 and H3BO3, which are volatile at 300 °C. Chakrabarti et al [16] discuss that O could become dissolved in microvoids in the film after deposition, but also states that it is unlikely that this can be the whole reason and that most of the O probably originates from the incorporation of residual gases such as H2O and CO2 during deposition.…”
Section: Chemical Bonding Structure and Elemental Compositionmentioning
confidence: 99%
“…The prospect of growing epitaxial films with well-defined properties in combination with the ceramic metallic characteristics demonstrated by ZrB2 makes it interesting as a thin film electrical contact material for demanding applications. Hitherto, growth on GaN(0001) has been investigated [2][3][4][5][6], whereas growth on 4H-SiC(0001) remains to be demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…Results on growth of films with composition deviating, sometimes substantially, from the composition of the utilized source, as well as growth of films with a high level of contaminants have been reported [2,4,6,10,[14][15][16][17][18]. The presence of a foreign element such as oxygen during nucleation of ZrB2 is likely to cause unwanted chemical reactions between the film constituents and the contaminant.…”
Section: Introductionmentioning
confidence: 99%
“…8 Our group previously reported improvement of SiC Schottky diodes by depositing various metal contacts at elevated temperatures. [15][16][17] Improvements in the contacts were explained in terms of removal of unwanted oxides at the interface and the formation of silicides with higher work functions. In this paper, we investigated the effect of Ti Schottky contact deposition temperature on the Ti/SiC Schottky barrier diodes, which, as far as we know, has not yet been conducted.…”
Section: Introductionmentioning
confidence: 99%